Clinical and Molecular Epidemiological Features of Hemorrhagic Fever with Renal Syndrome in Korea over a 10-year Period - Noh, Ji Yun (2013)
BACKGROUND: Laboratory diagnosis of hemorrhagic fever with renal syndrome (HFRS), an infectious disease caused by rodent-borne hantaviruses in Asia and Europe, depends primarily on serological methods. Since the advent of such serodiagnostic tests, few reports are available about the clinical and molecular epidemiological features of HFRS. OBJECTIVES: To investigate the epidemioclinical features of HFRS treated at a tertiary-care teaching hospital in Seoul over a 10-year period. STUDY DESIGN: Medical records of HFRS patients, visited to a tertiary-care teaching hospital during February 2002 to February 2012, were reviewed. Sera from patients were tested for Hantaan virus (HTNV) and Seoul virus (SEOV) RNA using RT-PCR. RESULTS: Among 35 HFRS patients (mean age was 44.2 ± 14.7 years), 29 were male (82.9%). Acute renal failure developed in 27 patients (77.1%), and 12 patients (34.3%) were admitted to the intensive care unit (ICU). Conjunctival injection (OR 10.32, 95% CI 1.09–97.77, P = .04) and initial serum albumin less than 3 g/dL (OR 22.83, 95% CI 1.45–359.93, P = .03) were risk factors for ICU admission. Of 35 acute-phase sera, 11 (31.4%) were positive for HTNV RNA. None were positive for SEOV RNA. CONCLUSIONS: HFRS was characterized by the clinical triad of fever, renal insufficiency and gastrointestinal symptoms. Conjunctival injection and serum albumin level were related to severity. Large scaled multi-center study is needed to enhance an insight to epidemioclinical characteristics of HFRS in Korea.